A PHYSICOCHEMICAL MODEL FOR NATIVE SULFUR MELT FORMATION AT A HOT LAKE BOTTOM - Karpov G.A.; Kazmin L.A.; Osipov V.P. (My University, 1998)
The results of the five-year monitoring of the condition of a thermal lake with molten sulfur at the bottom in the Uzon caldera (Kamchatka) (measurements of the temperature, depth, and thickness of the melt zone and of the pH values of the lake water and its free and dissolved gases) were used to derive a thermodynamic model for phase equilibria in the gas-water(steam)-sulfur(melt) system at 138°C and 4.5 bar. Calculations showed that the native sulfur melt could form at the bottom of a volcanic lake as a result of the inflow of mantle fluids enriched in H2S and SO2. Numerical modeling proved that a condensed sulfur phase, an aqueous solution, and a steam-gas phase containing appreciable amounts of H2S2, COS, S6, and S8 in addition to H2S and SO2 could exist in equilibrium under the observed conditions.